Influences of Retail Chains’ Sales Promotions on the Hungarian FMCG Markets - Pénzes, Ibolya Rózsa (The Hungarian Journal of Marketing and Management, 2019)
The behaviour of FMCG marketers is more and more influenced by the intensive sales promotion activity of store chains. This activity has a direct influence on the one hand on quantity and pattern of consumption, on the other hand on buying habits; but it also has an indirect influence on the competitors. Aim of this paper is to demonstrate the distinctiveness of store chain dependent SP system on domestic FMCG market and their influence on the consumers. The scope of this paper is to introduce the effect of regular periodical rebates via a primer research queried in East Hungary.